Save more tomorrow, today: experimental evidence on the role of precommitment, urgency, and personalization - Freeman, Charlton “Eli”; Skimmyhorn, William (Review of Finance, 2025)
Abstract We study the causal effects of precommitment framing, motivational deadlines, and semi-personalized information on military servicemembers’ retirement savings using a randomized field experiment. Low-cost emails highlighting a motivational deadline or semi-personalized salary information increased participation by about 1 percentage point (control mean is 1.25 percent) and contribution rates by about 0.05 percentage points (control mean is 3.92 percent) among previous non-participants. These programs demonstrate a cost-effective and scalable tool by which managers can increase employees’ retirement savings.